Intramural Venous Ethanol Infusion for Refractory Ventricular Arrhythmias: Outcomes of a Multicenter Experience - Tavares, Liliana; Lador, Adi; Fuentes, Stephanie; Da-Wariboko, Akanibo; Blaszyk, Krzysztof; Malaczynska-Rajpold, Katarzyna; Papiashvili, Giorgi; Korolev, Sergey; Peichl, Petr; Kautzner, Josef; Webber, Matthew; Hooks, Darren; et al. (JACC. Clinical electrophysiology, 2020)
OBJECTIVES: The aim of this study was to assess the long-term efficacy and outcomes of retrograde venous ethanol ablation in treating ventricular arrhythmias (VAs). BACKGROUND: Retrograde coronary venous ethanol ablation (RCVEA) can be effective for radiofrequency ablation (RFA)-refractory VAs, particularly those arising in the LV summit (LVS). METHODS: Patients with drug and RFA-refractory VAs were considered for RCVEA after RF failure attempts. Intramural coronary veins (tributaries of the great cardiac, anterior interventricular, lateral cardiac, posterolateral, and middle cardiac) were mapped using an angioplasty wire. Ethanol infusion was delivered in veins with appropriate signals. RESULTS: Of 63 patients (age 63 ± 14 years; 60% men) with VAs (71% extrasystole, 29% ventricular tachycardia, 76% LVS origin), RCVEA was performed in 56 patients who had suitable vein branches. These were defined as those amenable to cannulation and with intramural signals that preceded those mapped in the epicardium or endocardium and had better matching pace maps or entrainment responses. Seven patients had no suitable veins and underwent RFA. In 38 of 56 (68%) patients, the VAs were successfully terminated exclusively with ethanol infusion. In 17 of 56 (30%) patients, successful ablation was achieved using ethanol with adjunctive RFA in the vicinity of the infused vein due to acute recurrence or ethanol-induced change in VA morphology. Overall, isolated or adjuvant RCVEA was successful in 55 of 56 (98%) patients. At 1-year follow-up, 77% of patients were free of recurrent arrhythmias. Procedural complications included 2 venous dissections that led to pericardial effusions. CONCLUSIONS: RCVEA offers a significant long-term effective treatment for patients with drug and RF-refractory VAs.
Keywords: Tachycardia, Ventricular; ethanol; srdeční arytmie; Male; ventricular arrhythmias; výsledek terapie; Middle Aged; Ethanol; mužské pohlaví; Pericardium; Arrhythmias, Cardiac; ženské pohlaví; Humans; lidé středního věku; perikard; Female; Treatment Outcome; komorová tachykardie; lidé; catheter ablation